Factors affecting the level of commercialization of smallholder pig farmers in the west rand district municipality of gauteng, South Africa - G, Pule; DL, Mthombeni; MJ, Mamashila (Asian Journal of Agriculture and Rural Development, 2024)
This study aimed to analyse the factors influencing the smallholder pig farmers’ level of commercialization in the agricultural markets in the West Rand District of Gauteng Province, South Africa. A total population sampling was used, where data was collected from 84 smallholder pig farmers by a semi-structured questionnaire. Version 28.0 of the Statistical Package for Social Science (SPSS), binary logistic regression, and multinomial logit models were used to analyse the collected data. The results showed that 78.6% of the smallholder pig farmers lacked commercialization. The results further indicated that the pig unit size, level of the farmers’ commercialization, number of piglets per sow, and farmers’ affiliation had a significant influence on the smallholder pig farmers’ access to high-value markets. Variables such as credit availability, market accessibility, and the quantity of the piglets per sow significantly impacted the level of commercialization among the interviewed smallholder pig farmers. Smallholder farmers’ access to commercial and high-value pig markets is not easily accessible; therefore, the municipalities and local agricultural departments should make provision for an agricultural extension program that will prioritize and concentrate on the smallholder farmers’ access to the high-value market.